15.9k views
5 votes
Find the remainder when f(x)=x3−4x2−6x−3 f ( x ) = x 3 − 4 x 2 − 6 x − 3 is divided by x+1

1 Answer

3 votes

Answer:

The remainder is -2.

Explanation:

According to the Polynomial Remainder Theorem, if we divide a polynomial P(x) by a binomial (x - a), then the remainder of the operation will be given by P(a).

Our polynomial is:


P(x) = x^3-4x^2-6x-3

And we want to find the remainder when it's divided by the binomial:


x+1

We can rewrite our divisor as (x - (-1)). Hence, a = -1.

Then by the PRT, the remainder will be:


\displaystyle\begin{aligned} R &= P(-1)\\ &=(-1)^3-4(-1)^2-6(-1)-3 \\ &= (-1)-4(1)+(6)-3 \\ &= -2 \end{aligned}

The remainder is -2.

User Cbascom
by
5.0k points